Contemporizing Islamic Architecture: Adaptive Design in Middle Eastern and Central Asian Mosques - Ahamad, Shameel; Yasmoon, Zahra (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2024)
This study investigates the impact of globalization on contemporary Islamic architecture within the religious building typology in regions spanning Middle Eastern and Central Asia. The primary objective is to scrutinize the transformative paradigm by assessing its equilibrium between functional requisites and the preservation of cultural heritage, thereby elucidating common threads and regional differentiations. Methodologically, the research employs a comprehensive approach encompassing case studies, literature reviews, and meticulous photo analysis to elucidate the intricacies of modern Islamic architectural exemplars. It involved developing a conceptual framework and reviewing previous studies to build a theoretical foundation. This was then applied to selected projects. Key findings were that the spirituality of Islamic decorative designs stems from aesthetics linking form and meaning. Spirituality implies an inner vitality and timelessness. Contemporary materials and methods can retain the authenticity of Islamic decoration if the content and meaning are preserved. Through this examination, the research aims to uncover an insight into the socio-cultural ramifications of architectural evolution. By synthesizing multifaceted perspectives, this study provides a robust foundation for architects. It offers scholars and enthusiasts a nuanced comprehension of the processes underpinning the contemporizing of religious edifices within diverse cultural contexts.